An Open-Label, Randomized, Two-Period Crossover Study of the NuvaRing Applicator in Healthy Women [8N]. (May 2016) - Feldman, Robert; Frenkl, Tara; Yacik, Carol; Wang, Yinna; Fox, Michelle
Abstract : INTRODUCTION: NuvaRing®, a contraceptive vaginal ring, is inserted by the user with her fingers. An applicator has been developed as an optional insertion aid. This study assessed performance, tolerability, and safety of a new applicator. METHODS: Women aged 18–45 years not currently using NuvaRing® were enrolled at 2 centers in this 2-period crossover study. Women were randomly assigned to either applicator or fingers in the first period and the other method in the second. For both periods, the ring was in place for 24–72 h; questionnaires were administered immediately following ring insertion and at removal. The second period occurred 48–72 h after removal of the first ring. RESULTS: 164 women (mean age 30.2 years) were randomized: 163 completed the applicator period, 162 completed the fingers period. Insertion was 100% successful with both methods. Ring expulsion occurred in 1 and 2 women, respectively, with applicator and fingers. Among randomized subjects, 8.6% and 4.3%, respectively, reported at least 1 treatment-related adverse event (AE); all were mild and were mostly considered related to the ring rather than the insertion method. Five AEs (4 events [2.5%] of vulvovaginal pain, 1 episode [0.6%] of abdominal cramping) were considered related to the applicator. The 4 AEs of mild pain (eg, "pinching") lasted less than 1 minute and resolved spontaneously. Bleeding did not occur during or up to 15 h following applicator use; mild events occurred more commonly during follow-up after applicator use (3.1% and 0.6%, respectively). CONCLUSION: The NuvaRing® Applicator is an effective and well-tolerated optional NuvaRing® insertion aid.